A Review of Pancasila under Globalization - Shofi Munawwir Effendi (University of Jember, 2019)
Pancasila dalam Pusaran Globalisasi (Pancasila under Globalization) is a book that aims to see Pancasila, Indonesia's state ideology, from a global perspective. This book suggests readers consider the role of Pancasila over the world's powers of other ideologies by presenting rare insights to discuss and bridge the understanding of continuities and changes that has existed in society. Changes include, but not limited, to social, political, economic change, and linkages with various variations of society. Those changes are massively happening in the era of globalization plus with the challenges of the government to filter it. This book is a compilation of writings from various excellent academics in their fields. Moh. Mahfud MD, foremost Indonesia's professor of law and politics, delivered the book's prologue, who critically questioned 'Is Pancasila still relevant?' in the era for which Pancasila is rarely seen to implement in public life. Given the fact that hitherto Indonesia has faced problems that have come out of the nature of Pancasila. Mahfud, in his prologue, asked the reader to reflect on the true meaning of Pancasila. In short, understanding the role of Pancasila in this globalized world, particularly as the nation's ideology, has become essential so that every Indonesian citizen will have a much more similar understanding, perception, and attitude towards Pancasila.